The Effect of Viral Promotional Advergames on the Behavioral Reactions - Mostafa Heidari Haratemeh (‫مدیریت بازرگانی)
Objective Viral promotional advergames combine a promotional game with an advergame in a viral marketing campaign, aiming to encourage customer word of mouth, so that customers become willing promoters of the related brand. When designing a viral promotional advergame, marketers focus on game schemes and prizes to trigger players' intrinsic and extrinsic motivations and elicit certain behavioral responses, such as sharing personal data and forwarding the game. Therefore, the current research aimed to investigate how intrinsic playfulness and the extrinsic value of prizes affect people's behavioral responses. This research used data from pre-measure and post-measure assessments within a real viral marketing campaign. This field study examines the factors that lead to behavioral reactions in these types of games. In this connection, Poisson regression was used to investigate the effect of perceived playfulness and the perceived value of prizes on the variable of game forwarding, while logistic regression was used for the variable of personal data sharing.